Pain Neuroscience Education Reduces Pain and Improves Psychological Variables but Does Not Induce Plastic Changes Measured by Brain-Derived Neurotrophic Factor (BDNF): A Randomized Double-Blind Clinical Trial - Di-Bonaventura, Silvia; Donado-Bermejo, Aser; Montero-Cuadrado, Federico; Barrero-Santiago, Laura; Pérez-Pérez, Lucía; León-Hernández, José Vicente; Fernández-Carnero, Josué; Ferrer-Peña, Raúl (Healthcare (Basel), 2025)
Introduction: PNE, focusing on cognitive aspects, aims to change patients’ beliefs about pain. However, it is unclear if these cognitive changes are sufficient to influence other components such as neuroplastic changes. Objective: To assess whether 3-h pain neuroscience education (PNE) can induce changes in brain-derived neurotrophic factor (BDNF) levels and pain intensity in chronic pain patients. Methods: A double-blind randomized clinical trial was conducted with 66 participants aged 18–65 years old (50.86 ± 8.61) with chronic primary musculoskeletal pain divided into two groups: an intervention group receiving 3-h PNE lecture and a control group that received an educational booklet. Primary outcomes included plasma BDNF levels and perceived pain intensity (VAS). Secondary outcomes included anxiety (HADS-A), depression (HADS-D), catastrophizing (PCS), kinesiophobia (TSK), stress (PSS), and knowledge about pain. Measurements were taken in both groups before and after a three-hour intervention. Data were analyzed using paired t-tests and Cohen’s d for effect sizes. Results: The results showed no significant changes in BDNF levels for the PNE lecture group (p = 0.708) or the educational booklet group (p = 0.298). Both groups showed significant reductions in pain intensity (PNE: p < 0.001, d = 0.70; booklet: p = 0.036, d = 0.39). Secondary variables, such as knowledge (PNE: p < 0.001, d = −0.972; booklet: p < 0.001, d = −0.975) and anxiety (PNE: p < 0.001, d = 0.70; booklet: p = 0.035, d = 0.39), also showed significant improvements. Conclusions: PNE did not significantly change BDNF levels but effectively improved pain intensity, pain-related knowledge, and other clinical variables. These findings suggest that while PNE has cognitive benefits, it may not be sufficient to induce immediate neurobiological changes. Further research is needed to explore long-term effects and incorporate additional therapeutic domains.